Afforestation to mitigate climate change: impacts on food prices under consideration of albedo effects. (27th July 2016) - Kreidenweis, Ulrich; Humpenöder, Florian; Stevanović, Miodrag; Bodirsky, Benjamin Leon; Kriegler, Elmar; Lotze-Campen, Hermann; Popp, Alexander
Abstract: Ambitious climate targets, such as the 2 °C target, are likely to require the removal of carbon dioxide from the atmosphere. Afforestation is one such mitigation option but could, through the competition for land, also lead to food prices hikes. In addition, afforestation often decreases land-surface albedo and the amount of short-wave radiation reflected back to space, which results in a warming effect. In particular in the boreal zone, such biophysical warming effects following from afforestation are estimated to offset the cooling effect from carbon sequestration. We assessed the food price response of afforestation, and considered the albedo effect with scenarios in which afforestation was restricted to certain latitudinal zones. In our study, afforestation was incentivized by a globally uniform reward for carbon uptake in the terrestrial biosphere. This resulted in large-scale afforestation (2580 Mha globally) and substantial carbon sequestration (860 GtCO2 ) up to the end of the century. However, it was also associated with an increase in food prices of about 80% by 2050 and a more than fourfold increase by 2100. When afforestation was restricted to the tropics the food price response was substantially reduced, while still almost 60% cumulative carbon sequestration was achieved. In the medium term, the increase in prices was then lower than the increase in income underlying our scenario projections. Moreover, our results indicate that more liberalised trade in agricultural commodities could buffer the food price increases following from afforestation in tropical regions.